Criminal Responsibility of Criminal Acts of Hate Speech Through Social Media - Marbun, Tua Napitulu Warasman; Hartanto (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The development of information technology has changed the lifestyle of Indonesian people, including expressing their opinions through various social networking sites such as Facebook, Instagram, Twitter, WhatsApp and various other types of social media. The research method used isNormative legal research is a legal research method that examines applicable legal provisions.Freedom to express written and oral opinions has become the right of every Indonesian citizen which is regulated in Article 28 of the 1945 Constitution of the Republic of Indonesia. In this era, people can easily access social media and express their opinions. Every opinion must be accountable and must not conflict with existing norms. Unlimited freedom of opinion can result in criminal acts of hate speech. Case Study of Decision Number 914/Pid.Sus/PN.Jkt.Pst and Decision Number 63/Pid.Sus/2019/PN.Sdw, where in both cases the decision involved criminal acts of hate speech. The crime of hate speech in Indonesia has not been specifically regulated in any statutory regulations. Criminal liability for perpetrators of criminal acts of hate speech on social media is generally regulated in the Criminal Code (KUHP) and in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions.